2014
DOI: 10.1111/ans.12688
|View full text |Cite
|
Sign up to set email alerts
|

Is there an alternative to centralization for pancreatic resection in New Zealand?

Abstract: Acceptable outcomes have been achieved for patients undergoing pancreatic resection within a centre that meets the criteria proposed by the NZ National Standards for treatment of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…This emphasizes that, in New Zealand, pancreatic surgery takes place in hospitals with significant acute service commitments rather than dedicated elective surgical institutions, as is in Europe and North America. However, the finding of longer‐than‐anticipated hospital stays has resulted in the development of an enhanced recovery programme for patients undergoing pancreatic resection with the aim of reducing total admission times to 10 days or less …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasizes that, in New Zealand, pancreatic surgery takes place in hospitals with significant acute service commitments rather than dedicated elective surgical institutions, as is in Europe and North America. However, the finding of longer‐than‐anticipated hospital stays has resulted in the development of an enhanced recovery programme for patients undergoing pancreatic resection with the aim of reducing total admission times to 10 days or less …”
Section: Discussionmentioning
confidence: 99%
“…However, while national tumour‐specific management guidelines have been recently published, there are little New Zealand‐specific data available to guide the development of such centres. In particular, only one unit has published volume and outcome data for pancreatic resections, and no data are available with regards to national numbers and locations of pancreatic resections, costs and trends in management.…”
Section: Introductionmentioning
confidence: 99%
“…Oesophageal and pancreatic cancers are significant health problems and rank among the top 10 causes of cancer death worldwide . In the main, surgical resection is the only curative treatment option for these malignancies, but is complex with 30‐day mortality rates following oesophagectomy reported to range between 2.6% and 10%, while for pancreaticoduodenectomy mortality ranges between 2.6% and 6.3% …”
Section: Introductionmentioning
confidence: 99%
“…1 In the main, surgical resection is the only curative treatment option for these malignancies, but is complex with 30-day mortality rates following oesophagectomy reported to range between 2.6% and 10%, [2][3][4][5] while for pancreaticoduodenectomy mortality ranges between 2.6% and 6.3%. [6][7][8][9] In European and North-American population-level studies, significant improvements in post-operative mortality have been reported following oesophagectomy and pancreaticoduodenectomy performed in high-volume compared with low-volume centres; [10][11][12][13][14] and has led to the centralization of these procedures to high-volume hospitals in the UK, the Netherlands and Scandinavia. [15][16][17][18] By comparison, population-level studies in Australia have not reported improved post-operative mortality with higher hospital-volume following pancreaticoduodenectomy, 19 while for oesophagectomy, reports of improved mortality with higher surgical volumes are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…The recent article by Hore et al 1 describes the outcomes for pancreatic resections from one surgeon in a regional hospital. The outcomes are highly commendable and are used to argue that centralization is unnecessary.…”
mentioning
confidence: 99%